The Dynamics of Disability and Work in Britain. (2nd December 2016) - Jones, Melanie K.; Davies, Rhys; Drinkwater, Stephen
Abstract : This paper examines the dynamic relationship between work‐limiting disability and labour market outcomes using longitudinal data created by matching individuals in the Local Labour Force Survey (2004–10). By applying event‐study methods, changes in employment are traced through the onset of, and exit from, disability. These relationships are examined between subgroups of the population, including those defined by the nature and severity of disability. For most groups we find evidence of asymmetry in the impact of onset and exit: employment is significantly reduced at onset and continues to decline post‐onset whereas, after controlling for unobserved heterogeneity, exiting disability has a limited effect.